Immune regulation of the gut-brain axis and lung-brain axis involved in ischemic stroke - Xie, Xiaodi; Wang, Lei; Dong, Shanshan; Ge, ShanChun; Zhu, Ting (Neural regeneration research, 2024)
Local ischemia often causes a series of inflammatory reactions when both brain immune cells and the peripheral immune response are activated. In the human body, the gut and lung are regarded as the key reactional targets that are initiated by brain ischemic attacks. Mucosal microorganisms play an important role in immune regulation and metabolism and affect blood-brain barrier permeability. In addition to the relationship between peripheral organs and central areas and the intestine and lung also interact among each other. Here, we review the molecular and cellular immune mechanisms involved in the pathways of inflammation across the gut-brain axis and lung-brain axis. We found that abnormal intestinal flora, the intestinal microenvironment, lung infection, chronic diseases, and mechanical ventilation can worsen the outcome of ischemic stroke. This review also introduces the influence of the brain on the gut and lungs after stroke, highlighting the bidirectional feedback effect among the gut, lungs, and brain.